2023
DOI: 10.3390/ijms24119284
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib-Induced Cellular Senescence Is Modulated by the mTOR Complex 1 and Autophagy

Angel Cayo,
Whitney Venturini,
Danitza Rebolledo-Mira
et al.

Abstract: Despite not dividing, senescent cells acquire the ability to synthesize and secrete a plethora of bioactive molecules, a feature known as the senescence-associated secretory phenotype (SASP). In addition, senescent cells often upregulate autophagy, a catalytic process that improves cell viability in stress-challenged cells. Notably, this “senescence-related autophagy” can provide free amino acids for the activation of mTORC1 and the synthesis of SASP components. However, little is known about the functional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Additionally, dysfunction of TFEB, accompanied with impaired mitophagy, is associated with tubular senescence and renal fibrosis [ 46 ]. Chronic senescence of tubular epithelial cells exacerbates renal fibrosis by mTORC1-autophagy axis [ 47 , 48 ]. Huang and colleagues revealed that TXNIP deficiency attenuates diabetes-induced blockage of tubular autophagic flux via suppressing mTOR in diabetic rat kidneys [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dysfunction of TFEB, accompanied with impaired mitophagy, is associated with tubular senescence and renal fibrosis [ 46 ]. Chronic senescence of tubular epithelial cells exacerbates renal fibrosis by mTORC1-autophagy axis [ 47 , 48 ]. Huang and colleagues revealed that TXNIP deficiency attenuates diabetes-induced blockage of tubular autophagic flux via suppressing mTOR in diabetic rat kidneys [ 14 ].…”
Section: Discussionmentioning
confidence: 99%